2021
DOI: 10.1111/1346-8138.15807
|View full text |Cite
|
Sign up to set email alerts
|

Long‐standing refractory hidradenitis suppurativa responded to a brodalumab monotherapy in a patient with psoriasis: A possible involvement of Th17 across the spectrum of both diseases

Abstract: Hidradenitis suppurativa (HS) is a chronic autoinflammatory suppurativa condition of dyskeratinization where the targeted skin component involves abnormal regulation of cytokine flux. Several lines of evidence suggest that inflammatory cytokines such as TNFα, IL-1β, and IL-17 are considered to play a coordinating role in the pathogenesis of HS. 1 Biologics antagonizing these cytokines may offer a promising nonsurgical approach in the refractory disease. Of these, TNFα inhibitors adalimumab and infliximab have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Of the 311 studies identified, 36 full texts were assessed for eligibility and 16 met inclusion criteria, representing 128 patients (mean age: 36.5 years; age range: 21-47 years; male: 50.0%) (Supplemental File 5-6). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Studies included 9 case reports, 4 cohort studies and 3 clinical trials. Level of evidence analysis yielded 9 studies with a level of evidence of 5, 4 studies with level of evidence of 2, and 3 studies with level of evidence of 1.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…Of the 311 studies identified, 36 full texts were assessed for eligibility and 16 met inclusion criteria, representing 128 patients (mean age: 36.5 years; age range: 21-47 years; male: 50.0%) (Supplemental File 5-6). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Studies included 9 case reports, 4 cohort studies and 3 clinical trials. Level of evidence analysis yielded 9 studies with a level of evidence of 5, 4 studies with level of evidence of 2, and 3 studies with level of evidence of 1.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…Brodalumab is typically dosed at 210 mg weekly for 2 weeks, then every 2 weeks thereafter. Three case reports utilizing this dosage regimen reported improvement of HS in all three patients, two of whom had comorbid psoriasis that improved as well 22,103,104 . An open‐label study of 10 patients using this dosing regimen achieved HiSCR in 100% of patients by Week 12 105 .…”
Section: Il‐17 Inhibitorsmentioning
confidence: 86%
“…BRO has shown promising results in three case reports, 133,150,151 and two phase I open-label trials have been conducted. An open-label cohort study included 10 patients with moderate-to-severe HS who were treated with BRO 210 mg sc at weeks 0, 1, and 2 and every 2 weeks thereafter until week 24.…”
Section: Treatmentmentioning
confidence: 99%